2023
DOI: 10.1681/asn.0000000000000141
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Human Kidney Tissue Proteomics Identifies Matrix Metalloproteinase 7 as a Kidney Disease Biomarker

Abstract: Significance Statement Although gene expression changes have been characterized in human diabetic kidney disease (DKD), unbiased tissue proteomics information for this condition is lacking. The authors conducted an unbiased aptamer-based proteomic analysis of samples from patients with DKD and healthy controls, identifying proteins with levels that associate with kidney function (eGFR) or fibrosis, after adjusting for key covariates. Overall, tissue gene expression only modestly correlated with tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The Mendeley data set contained 33 human kidney cortical samples: 23 samples from patients with DKD and 10 from healthy participants ( https://data.mendeley.com/datasets/83k89shdx5/ ). Detailed demographics of the study sample have been described previously ( 4 ). Differential protein expression results show that AKR1A1 levels were significantly lower in patients with DKD compared with healthy control participants (FDR = 0.029; log 2 FC = −0.61; see Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mendeley data set contained 33 human kidney cortical samples: 23 samples from patients with DKD and 10 from healthy participants ( https://data.mendeley.com/datasets/83k89shdx5/ ). Detailed demographics of the study sample have been described previously ( 4 ). Differential protein expression results show that AKR1A1 levels were significantly lower in patients with DKD compared with healthy control participants (FDR = 0.029; log 2 FC = −0.61; see Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Hirohama et al. ( 4 ) identified, via unbiased human kidney tissue proteomics, matrix metalloproteinase 7 (MMP7) as a diagnostic marker of kidney fibrosis and blood MMP7 as a biomarker for future kidney function decline in patients with DKD.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42][43] A recent kidney tissue proteomics study identified MMP-7 as a kidney disease biomarker that correlated with fibrosis and predicted faster eGFR decline. 44 The role of MMP-7 in kidney disease appears to be multifactorial. MMP-7 knockout mice show reduced collagen deposition, reduced interstitial fibrosis, but increased albuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs), pivotal in processes such as development, inflammation, tissue repair, and angiogenesis, contribute to renal TIF through mechanisms involving EMT and TGF-β signaling pathways 6,7 . Specifically, MMP-7 and MMP-9 facilitate extracellular matrix remodeling [8][9][10] . Sato et al first identified membrane type matrix metalloproteinases(MT-MMP), and believed that they have a dual effect of activate other MMPs and degrade the extracellular matrix 11,12 .…”
Section: Introductionmentioning
confidence: 99%